The Correlation of Initial Sputum Smear Positivity on Treatment Failure of Category 1 Therapy for Pulmonary Tuberculosis - Puput Dyah Ayu; Muhammad Atoillah Isfandiari (Universitas Airlangga, 2016)
Tuberculosis (TB) is an infectious disease and is an important public health problem. Based on data in the East Java Provincial Health Office in 2014 the highest number of TB sufferers was Surabaya. Transmission can be controlled by the discovery and good healing. The discovery and cure are based on the results of the patient's sputum examination, therefore examination of sputum with direct microscopic acid-resistant bacteria (BTA) becomes fundamental. This study was conducted to determine the relationship between the level of positivity of the initial acid-fast bacilli with the failure of treatment of the Anti-Tuberculosis Drugs (OAT) 1st category in the Paru Hospital of Surabaya in 2011-2014. This research is quantitative research with a case-control study design. The total sample of 42 respondents obtained from secondary data. The sample of 21 respondents who experienced a failure of OAT 1st category treatment as a group of cases and 21 respondents who recovered in OAT 1st category treatment as a control group. Sampling using a simple random sampling technique. Analysis using a chi-square test. The results showed that the high initial BTA positivity level (p = 0.045; OR = 5.4) had a significant relationship and risk with OAT 1st category treatment failure. In conclusion, the high initial BTA positivity rate associated with the failure of the OAT 1st category at the Paru Hospital in Surabaya in 2011-2014. There needs to be increased supervision of treatment for pulmonary TB patients who have a high initial BTA positivity rate.